Carreer Aspirations of R&D Professionals in Government Research Institutes and Multinational Corporations in Malaysia - Ismail, Maimunah; Ramly, Efizah Sofiah (Organizations and Markets in Emerging Economies, 2010)
The research compares the influence of self-efficacy, organizational socialization and continuous improvement practices on career aspirations of research and development (R&D) professionals of government research institutes (GRIs) and multinational corporations (MNCs) in Malaysia. This study used Social Cognitive Career Theory (SCCT) to examine the influence of the selected variables on career aspirations of the R&D professionals. Data were collected from 164 respondents from GRIs and 120 respondents from MNCs in the country. The data were analyzed using descriptive statistics and multiple linear regressions. The two groups differed significantly in terms of their levels of self-efficacy and organizational socialization, and were not significantly different in continuous improvement practices and career aspirations. Self-efficacy and organizational socialization levels of R&D professionals in GRIs were found to be slightly higher than those of MNCs. Regression results showed MNCs reported higher explanatory power compared to that of the GRIs in terms of variance in career aspiration. This study suggests that continuous improvement practices and self-efficacy are relevant to the model of SCCT. Managers and human resource development (HRD) practitioners in both types of organizations need to restructure the work practices of R&D professionals by strengthening the quality improvement work procedures and cognitive-behaviour initiatives.